Liquid chromatography- tandem mass spectrometric method for simultaneous determination of rutin and quercetin from leaves of artocarpus lakoocha roxb. - VIKAS; ASHISH RAOTE; ARVIND JANGID; RAJESH TALE; VIKAS (International Journal of Pharma and Bio Sciences, 2011)
Artocarpus lakoocha Roxb. is a valuable tropical tree species native to India and used for fruit, furniture, timber, and feed. Artocarpus lakoocha Roxb. contains a crude protein, crude fiber and mineral contents. A rapid, reproducible and efficient liquid chromatography-tandem mass spectrometry (LC-MS/MS) method has been developed to quantify Rutin and Quercetin simultaneously from Artocarpus lakoocha Roxb. leaves. The analytes were chromatographed on a Hypurity C18 (50mm x 4.6mm i.d., 5 µ particle size) column using 10µL injection volume with a run time of 5 min. The precursor and product ion of analytes were monitored on a triple quadrapole mass spectrometer, operating in the multiple reaction monitoring mode (MRM) with negative polarity. The proposed method was validated over the range of 0.5 ng/ml to 100.0 ng/ml. The proposed LC-MS/MS method was validated for linearity, accuracy, precision and limit of quantitation